Peran Kepala Sekolah dalam Komunitas Belajar di Daerah Terpencil - Nur Aisyah Wani Aisyah; Priadi Surya (Kelola: Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the roles of the principal as a leader, supervisor, and motivator in developing a learning community at SMA Negeri 1 Belantikan Raya. The research is based on the observation that learning community activities in the school are still incidental and have not yet become part of a sustainable reflective culture among teachers. A qualitative phenomenological approach was employed, using in-depth interviews, participatory observations, and document analysis. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that the principal’s role as a leader is reflected in building a collaborative vision, strengthening instructional direction, and fostering a culture of teacher cooperation. As a supervisor, the principal provides academic guidance, facilitates reflective practices, and ensures systematic follow-ups to learning community outcomes. Meanwhile, the role as a motivator is demonstrated through emotional support, recognition, and encouragement that strengthens teachers’ commitment to continuous learning. The study also identifies several challenges, including limited facilities, variations in teacher competence, low consistency in reflective practices, and limited professional networks. These challenges were addressed through visionary leadership strategies, strengthened school policies, and expanded collaboration across learning communities. In conclusion, the principal plays a significant role in establishing a sustainable learning community. The integration of leadership, supervision, and motivation functions becomes a key determinant in fostering a collaborative culture that contributes to teacher professionalism and improved instructional quality.